Innovative Finance: Learning on CGIAR’s Ways of Working - Preissing, John; Theuri, George (CGIAR Independent Advisory and Evaluation Service, 2025)
This summary of learning, prepared under the System Council–endorsed Multi-Year Evaluation Plan (MYEP), synthesizes evidence on one of CGIAR’s Ways of Working (WoWs) identified in the CGIAR 2030 Research and Innovation Strategy as a priority approach for CGIAR to do business differently, namely: